The role of cutaneous T-cell attracting chemokine in the development of different phenotypes of atopic dermatitis in children - Dytiatkovsky , V.O.; Abaturov , O.Є.; Naumenko , N.V.; Alifirenko , O.O.; Filatova , I.A.; Taran , S.M. (Medicni Perspektivi, 2021)
The goal of this study was to detect the risk of developing different atopic dermatitis (AD) phenotypes in children (isolated or combined with other comorbid atopic diseases (AtD)) depending on serum concentrations of cutaneous T-cell attracting chemokine (CTACK)/CCL27. The main group comprised 39 children aged 3 to 18 years old suffering from different AD phenotypes – isolated (18 patients) and combined with comorbid AtD – AR/ARC and/or bronchial asthma (21 patients). The control group comprised 47 children aged 3 to 18 years old, suffering from diseases of the gastrointestinal tract (GIT). Serum CTACK/CCL 27 concentrations were detected in all children. In the full main group, the average level of CTACK/CCL27 was significantly higher compared to the patients of the control group: 4403.6 pg/ml (95% CI: 3726.2; 5148.7, p<0.001) and 3495.9 pg/ml (95% CI: 3197.8; 4186.8, p<0.001), respectively. Mean serum CTACK/CCL27 levels in patients of the main group with different AD phenotypes were higher than those in the full main group: with isolated AD – 4549.4 pg/ml (LQ; HQ: 3923.5; 5175.2, p<0.05), with AD associated with other AtD – 5116.6 pg/ml (LQ, HQ: 4062.8; 6170.5, p<0.05). In phenotypes of overall and isolated AD, the cut-off value of serum CTACK/ CCL27 is 3586.5 pg/ml (76.9% and 77.8%, respectively, and 38.3% in the control group). The risk of development at this concentration is 5.37 (95% CI: 2.05; 14.07, p<0.001) for the total AD phenotype and 5.64 (95% 1.56; 20.32, p<0.05) for the isolated AD phenotype. In AD phenotype combined with comorbid AtD, the cut-off value of serum CTACK/CCL27 is 4308.8 pg/ml (66.7% of the main and 21.3% in the control group). The risk of developing this AD phenotype at this concentration is 7.40 (95% CI: 2.30; 23.76, p<0.001). Serum CTACK/CCL27 levels are the reliable biomarker of the risk for developing different AD phenotypes in children. In the serum level of CTACK/CCL27=3658.5 pg/ml, the significant risk of developing total AD phenotype is 5.37, and isolated – AD=5.64. In the serum concentration of CTACK/CCL27=4308.8 pg/ml, the significant risk of developing AD phenotype combined with comorbid AtD is 7.40.